KARAKTERISASI SIFAT FISIK, KIMIA, DAN MEKANIK SERAT SELULOSA ALAMI DARI AMPAS TEBU - Andrianto, Sis Nanda Kus; Fitri, Femiana Gapsari Madhi; Wijayanti , Widya (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The demand for cellulose fibers is increasing due to their eco-friendly nature. Natural fibers have special qualities that make them excellent for a wide range of fibrous applications, including composites, nanomaterials, biomaterials, textiles, and conductive carbon, which are the main causes of the increased demand. This study uses sodium hypochlorite (NaOCl) and sodium hydroxide (NaOH) to chemically treat sugarcane bagasse fibers. The highest tensile strength, 532.12 MPa, was found in the fibers treated with both NaOCl and NaOH. Hemicellulose, lignin, and other contaminants were removed through chemical processing, according to a Fourier transform infrared (FTIR) study. According to the SEM pictures, the NaOCl and NaOH-treated fibers' surfaces improved in cleanliness and roughness. The NaOCl and NaOH treatments showed promise for creating nanocellulose from bagasse fibers and for strengthening composites.